Buy It Now Lessons from eBay - White, Michele (Duke University Press, 2012)
Buy It Now, Michele White examines eBay and its emphasis on community and social norms, revealing the cultural assumptions about gender, race, and sexuality that are reinforced throughout the site. She shows how instructional texts, rule systems, and advertisements "configure the user," allowing eBay to indicate how the site is supposed to function while also upholding particular values and practices. White details how eBay reinforces stereotypes about gender and sexuality, looking, for example, at descriptions included in wedding dress listings, and how eBay directs individuals to the "Adult Only" part of the website when they use the search terms "gay" and "lesbian." She discloses the ways that eBay promises a caring community but its "Black Americana" category reproduces racism by allowing sellers' narratives that excuse and romanticize slavery and insult African Americans. White also looks at how participants challenge eBay's categories, rules, and values, examining widely used strategies of resistance by sellers and buyers in the lesbian and gay interest listings. By analyzing the organizational and cultural logics present in eBay, White emphasizes how other Internet settings, including craigslist, are not as transparent, community-oriented, and empowering as they claim. She proposes methods for researching and reconceptualizing new media sites.